2014
DOI: 10.1038/onc.2014.156
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL-R2-specific antibodies and recombinant TRAIL can synergise to kill cancer cells

Abstract: TRAIL induces apoptosis in cancer cells whilst sparing normal tissues. Despite promising pre-clinical results, few patients responded to treatment with recombinant TRAIL (Apo2L/Dulanermin) or TRAIL-R2-specific antibodies, such as conatumumab (AMG655). It is unknown whether this was due to intrinsic TRAIL resistance within primary human cancers or insufficient agonistic activity of the TRAIL-R-targeting drugs. FcγR-mediated crosslinking increases the cancer-cell-killing activity of TRAIL-R2-specific antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 28 publications
(51 reference statements)
2
53
0
Order By: Relevance
“…Interestingly, the co-administration of LUV-TRAIL and DJR2 did not enhance apoptosis induction, suggesting that there was a maximum threshold of pro-apoptotic signaling to be achieved by DR5 clustering, and this was already reached with LUV-TRAIL alone. In this regard, it has been recently showed that combination of TRAIL with DR5-specific antibodies can synergize to kill cancer cells [24]. In that study, the authors concluded that simultaneous binding of both TRAIL and agonistic antibodies to death receptors resulted in enhanced DR5 cross-linking, causing an increased DISC recruitment, similar to our results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the co-administration of LUV-TRAIL and DJR2 did not enhance apoptosis induction, suggesting that there was a maximum threshold of pro-apoptotic signaling to be achieved by DR5 clustering, and this was already reached with LUV-TRAIL alone. In this regard, it has been recently showed that combination of TRAIL with DR5-specific antibodies can synergize to kill cancer cells [24]. In that study, the authors concluded that simultaneous binding of both TRAIL and agonistic antibodies to death receptors resulted in enhanced DR5 cross-linking, causing an increased DISC recruitment, similar to our results.…”
Section: Discussionsupporting
confidence: 89%
“…We achieved this by pre-incubating the cells with monoclonal specific DR4 and/or DR5 antibodies similar to the work recently described by Tuthill et al [24]. As shown in Fig.…”
Section: Luv-trail's Higher Pro-apoptotic Potential Relies On a Supermentioning
confidence: 96%
“…However, more recent studies have found that the combination of DR5-specific antibodies and hrTRAIL can synergize to kill cancer cells both in vitro (70,71) and in vivo (70). This combination therapy proved beneficial even in some previously TRAIL-resistant cancers.…”
Section: Tnfsf Ligands Are Essential For Tnfrsf Signaling-lessons Fromentioning
confidence: 99%
“…This could be attributed to the different sensitivity of tumors to TRAIL on one hand and to the limited activity of targeting molecules, due to the short half-life of recombinant TRAIL and the monospecificity of the agonistic antibodies (Abs), on the other (1,5). To ameliorate TRAIL activity, several formulations of recombinant TRAIL, such as fusion to poly-histidine, Flag and leucin Zipper tags, or linked to Fc portion of IgG, have been developed and are currently tested at preclinical level (6,7). The combination of recombinant TRAIL with chemotherapeutics, radiotherapy, small molecules, or natural compounds aimed at enhancing the sensitivity of cancer cells, have also found wide application in preclinical approaches (8,9).…”
Section: Introductionmentioning
confidence: 99%